Transformasi Hukum Acara Perdata dalam Era E-Court: Analisis Procedural Justice antara HIR/RBg dan PERMA No. 1 Tahun 2019 - Nanda Nosie Perdana Putri; Nadia Ummi Nabilah; Rizha Claudilla Putri (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
The development of information technology has encouraged transformation in the administration and implementation of the judicial system in Indonesia, including within civil procedural law. The civil justice process, which has traditionally relied on manual procedures as regulated in the HIR and RBg, faces several limitations such as lengthy procedures, relatively high costs, and limited access for justice seekers. To address these challenges, the Supreme Court introduced the e-court system as part of judicial modernization through the digitalization of case administration and court proceedings. This study aims to analyze the effectiveness of the implementation of e-court in realizing procedural justice within civil procedural law and to examine the relationship between the classical procedural provisions contained in HIR/RBg and the newer regulations governing electronic court administration. The research employs a normative legal research method using statutory and conceptual approaches by examining legal provisions and the concept of procedural justice within the judicial system. The findings indicate that the implementation of e-court reflects a paradigm shift in civil procedural law from a formalistic system toward a more digital and administrative system that improves efficiency in case administration and accelerates dispute resolution. However, this transformation also raises questions regarding the harmonization of legal norms between the regulations governing electronic court systems and the traditional civil procedural rules. Nevertheless, the implementation of e-court has positive implications for the realization of the principles of simple, fast, and low-cost justice while also improving public access to more effective and efficient judicial services.